Pengaruh Kualitas Pelayanan terhadap Kepuasan Pelanggan Miniso Big Mall Samarinda - Muhammad Rifqy Rifani; Andi Amri (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
This study aims to test whether the Quality of Laundry Service affects Patient Satisfaction in RSUD Kab. Kediri. This study used a quantitative descriptive approach with a causal research design applied to determine the cause-and-effect relationship between the independent variable (Laundry Service Quality) and the dependent variable (Patient Satisfaction). The study population consisted of 224 non-medical employees of Kediri District Hospital. Non-probability sampling techniques with purposive sampling types are used to determine samples based on certain criteria. Using the Slovin formula and the 5% error standard, a sample of 34 employees was obtained. Data were collected using the Likert scale and analyzed to test hypotheses. The results showed that the calculated value for the Laundry Service Quality variable was 7.970, which was greater than the ttable of 2.037, with a significant value of 0.000 which was smaller than 0.050. This shows that the Quality of Laundry Service has a significant effect on Patient Satisfaction, so the hypothesis (Ha) is accepted. The regression coefficient value of 0.563 indicates that an increase of one unit in Laundry Service Quality will increase Patient Satisfaction by 0.563 units, while a decrease of one unit in Laundry Service Quality will decrease Patient Satisfaction by 0.968 units. An R² value of 0.665 indicates that 66.5% of the variation in Patient Satisfaction is explained by Laundry Service Quality, while the remaining 33.5% is influenced by other variables not studied in this study.